Production of recombinant DNA fragmentation factor 40 in fusion to an antimicrobial peptide from spider venom and evaluation of its cytotoxic effects - Zahra Shafiee-Ardestani; Fatemeh Shafiee (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: DNA fragmentation factor 40 (DFF40) as an apoptotic molecule can represent a novel approach to cancer treatment. Lycosin-I (LYC-I), a peptide derived from spider venom, was considered for the targeted delivery of DFF40 to cancer cells. This study attempted to produce soluble DFF40-LYC-I and evaluate its selective lethal effects on HeLa cells. Experimental approach: pTWINl vector was used to produce LYC-I and DFF40-LYC-I in E. coli BL21 (DE3) fused to inteins 1 and 2. IPTG concentration and incubation temperature were optimized to achieve the highest level of soluble product. To remove inteins 1 and 2 from the recombinant peptide or protein, pH shift and dithiothreitol were used for a 24-h incubation period at room temperature, respectively. MTT assay was performed to assess the biological effects of these bio-molecules on HeLa and HUVEC cell lines. Findings/Results: LYC-I and DFF40-LYC-I were detected in SDS-PAGE with bands of approximately 57 and 97 kDa, respectively. Furthermore, the 3 and 43 kDa bands showed the purified molecules. The IC50 value of DFF40-LYC-I and DFF40 was determined as 6.6 and 17.03 μg/mL for HeLa, respectively. LYC-I had no cytotoxic effects on both cell lines, even at high concentrations. Conclusion and implications: A new fusion protein with targeted cancer treatment potential was produced for the first time by LYC-I with a safe profile on normal cells. This fusion protein exhibited higher cytotoxic effects in cancer cells compared to normal cells. However, additional investigations are required to determine the apoptosis induction and evaluate selective toxicity against other cancer and normal cell lines.